(untitled) (Research, Society and Development, 2019)
The objective of this article was to carry out a historical contextualization and a contemporary evaluation of cotton production in the state of Mato Grosso. In order to reach the proposed objective, bibliographic and documentary revision techniques were used. It was found that the state of Mato Grosso stands out as the main national producer of cotton in feather, which is an important raw material for the textile industry. However, when assessing the participation of Mato Grosso in the textile production at national level, it is irrelevant, accounting for only 0.64% of the number of industrial establishments in the country in 2017. Thus, it opens space for the discussion and proposition of new studies on the performance of the agroindustrial complex of Mato Grosso cotton, as for example, in the verification of which types of factors make difficult in the consolidation of the textile industry at the analyzed locality.